The dressmaker [videorecording (DVD)] - Moorhouse, Jocelyn, 1960-; Winslet, Kate; Davis, Judy, 1956-; Hemsworth, Liam, 1990- (Broad Green Pictures, 2016)
Tells the story of the beautiful and talented Tilly Dunnage. After years working as a dressmaker in exclusive Parisian fashion houses, Tilly returns home to a town in the Australian outback to reconcile with her eccentric mother Molly. She also falls in love with the pure-hearted Teddy, and armed with her sewing machine and haute couture style, Tilly transforms the women of the town, exacting sweet revenge on those who did her wrong.